2016
DOI: 10.1097/aog.0000000000001571
|View full text |Cite
|
Sign up to set email alerts
|

Association of Recorded Estimated Fetal Weight and Cesarean Delivery in Attempted Vaginal Delivery at Term

Abstract: Objective To evaluate the association between documentation of estimated fetal weight, and its value, with cesarean delivery. Methods This was a secondary analysis of a multi-center observational cohort of 115,502 deliveries from 2008 to 2011. Data were abstracted by trained and certified study personnel. We included women ≥37 weeks attempting vaginal delivery with live, non-anomalous, singleton, vertex fetuses, and no history of cesarean delivery. Rates and odds ratios were calculated for women with ultraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 11 publications
5
22
1
Order By: Relevance
“…In a retrospective cohort analysis, EFW was also associated with an increased risk for caesarean delivery (OR 1.44, 95% CI 1.1–1.9) [ 20 ]. Similar results were found in a recently published big cohort study of 64,030 women at term who attempted vaginal delivery [ 21 ]. In this study the knowledge of EFW was significantly associated with an increased risk of caesarean delivery (adjusted OR 1.44 (95% CI 1.31–1.58, P < 0.001).…”
Section: Discussionsupporting
confidence: 91%
“…In a retrospective cohort analysis, EFW was also associated with an increased risk for caesarean delivery (OR 1.44, 95% CI 1.1–1.9) [ 20 ]. Similar results were found in a recently published big cohort study of 64,030 women at term who attempted vaginal delivery [ 21 ]. In this study the knowledge of EFW was significantly associated with an increased risk of caesarean delivery (adjusted OR 1.44 (95% CI 1.31–1.58, P < 0.001).…”
Section: Discussionsupporting
confidence: 91%
“…In the case of suspected fetal macrosomia, systematic reviews have clarified that estimates of fetal weight are imprecise and frequently falsely identify large fetuses, and that induced labor for suspected fetal macrosomia does not improve outcomes . Furthermore, this practice has been associated with higher rates of cesareans . For these reasons, a long‐standing Practice Bulletin of the American College of Obstetricians and Gynecologists (ACOG), which was in effect when our survey participants gave birth and has recently been reaffirmed (2015), clarifies that suspected fetal macrosomia is not an indication for labor induction .…”
Section: Introductionmentioning
confidence: 76%
“…The IG standards would also classify more fetuses as LGA which could lead to unnecessary surveillance of these fetuses and possibly iatrogenic interventions, such as earlier delivery or caesarean. 32 Our finding that the differences in growth parameters between the sample restricted to women fulfilling the IG selection criteria and the overall population were very small is relevant for the current debate on growth standards vs. references. It shows that population selection is not an explanation for the differences between the IG standards and fetal growth in the ELFE cohort and is also unlikely to explain the differences found in other population-based studies.…”
Section: Femur Length Abdominal Circumferencementioning
confidence: 83%
“…requiring more surveillance because of potentially suboptimal growth; many professional societies recommend that monitoring small for gestational age (SGA) fetuses 1-3 and identifying large for gestational age fetuses are important for the surveillance of women with gestational diabetes and for the management of delivery. [29][30][31][32] Several studies have shown that failure to detect growth restriction among SGA fetuses is associated with higher rates of stillbirths and neonatal morbidity. [33][34][35] The IG standards would classify fewer fetuses as being SGA than the currently used references and could worsen performance, already judged to be sub-optimal, 29 for identifying SGA fetuses needing more surveillance.…”
Section: Femur Length Abdominal Circumferencementioning
confidence: 99%